Microbial and biogeochemical responses to projected future nitrate enrichment in the California upwelling system - Mackey, Katherine R. M.; Chien, Chia-Te; Paytan, Adina (Frontiers in Microbiology, 2014)
Coastal California is a dynamic upwelling region where nitrogen (N) and iron (Fe) can both limit productivity and influence biogeochemistry over different spatial and temporal scales. With global change, the flux of nitrate from upwelling is expected to increase over the next century, potentially driving additional oceanic regions toward Fe limitation. In this study we explored the effect of changes in Fe/N ratio on native phytoplankton from five currently Fe-replete sites near the major California upwelling centers at Bodega Bay and Monterey Bay using nutrient addition incubation experiments. Despite the high nitrate levels (13-30 M) in the upwelled water, phytoplankton at three of the five sites showed increased growth when 10 M nitrate was added. None of the sites showed enhanced growth following addition of 10 nM Fe. Nitrate additions favored slow sinking single-celled diatoms over faster sinking chain-forming diatoms, suggesting that future increases in nitrate flux could affect carbon and silicate export and alter grazer populations. In particular, solitary cells of Cylindrotheca were more abundant than the toxin-producing genus Pseudonitzschia following nitrate addition. These responses suggest the biogeochemistry of coastal California could change in response to future increases in nitrate, and multiple stressors like ocean acidification and hypoxia may further result in ecosystem shifts.